“Paradoxos do aggiornamento”: uma análise das narrativas dos padres sobre os impactos da modernidade religiosa no catolicismo do Cariri paraibano - Santos, Débora Maia Lacerda (2020)
With the advent of modernity, changes have occurred across the cultural, social, political, economic and religious world and this has directly affected the profile of society and its subjects. These, in turn, presented new personal and social needs, one of which was the need to choose in the face of effervescent religious plurality, and all these changes questioned the hegemonic position of the Catholic Church with regard to its determining power in the lives of individuals. The Catholic Church reacted to the idea of religious freedom and the consequences arising from it through a general world meeting, the Second Vatican Council, in which the spirit of aggiornamento during that Council promoted a change in the Catholic religious position leading the Institution to accept, value and even defend religious freedom for so many years fought and repudiated. Our research is based on the assumption that modernity has led the Catholic Church to recognize that the reality of religious pluralism and religious freedom are necessary historical conditions for the exercise of its mission in the world, as well as for a better understanding of this awareness by the Church. Catholic about the need for this aggiornamento, this process of “modernization of Catholicism”. That said, this study aimed to analyze the narratives of Catholic leaders from Cariri in Paraíba and their claims, interpreting and linking them with theories of renowned scholars on the themes of the “modernity and religion” sphere and culminated in the thesis that the adherence to Catholicism remains in the majority even in places where religious modernity also has a great impact. The present study had a qualitative and quantitative character, carried out a field research to better understand the current religious situation and used the data from the IBGE Census on the item - Religion - for a better understanding of this current religious plurality. Six priests from Cariri from Paraíba were interviewed and their narratives were screened by the sciences of religions in order to understand how these Catholic leaders face the impacts of modernity on Catholicism, what resources are alleged in an attempt to keep their faithful in their institution in the face of diversity current religion and how its profile of leader and its leadership in front of the Institution ensure the profile of the Catholic tradition most evident in the interior cities listed in this research.